Efeito antinociceptivo do monoterpeno tetrahidrolinalol em camundongos - Pazos, Natalia Diniz Nunes (2022)
Pain is a complex experience and represents a protection and survival mechanism, which can significantly impact the individual's quality of life. The treatment of this condition uses analgesic drugs, compounds with side effects that can impair the patient's well-being and adherence to treatment. In this sense, aromatic plants are sources of molecules that can serve as structural templates for the elaboration of substances with diverse pharmacological potential, such as tetrahydrolinalool (2,6-dimentyl-6-octanol), a monoterpene derived from linalool with antinociceptive activity. In this context, the aim of this study was to investigate the antinociceptive effect of tetrahydrolinalool (THL) through in silico and in vivo methodologies. Among the in silico methodologies, the molecular docking technique was used in order to prospect possible targets related to the antinociceptive effect of THL. In addition, in vivo methodologies were performed using male Swiss mice (Mus musculus), which were treated with THL (50, 100 and 200 mg.kg -1, v.o.) and submitted to rota-rod test and abdominal writhing models. by acetic acid, hot plate and formalin. The docking results revealed that THL showed affinity for the μ-opioid receptor (-55.6 Kcal/mol on Moldscore and -47.3 Kcal/mol on Plantscore) and for the transient vanilloid potential receptor type 1 (TRPV1) (- 40.9 Kcal/mol on Moldscore and - 34.1 Kcal/mol on Plantscore). Regarding the in vivo tests/models, THL had no effect on the motor coordination of the animals in the rota-rod test. On the other hand, THL treatment significantly reduced the number of abdominal writhing induced by acetic acid at doses of 50 mg.kg -1 (16.8 ± 4.5), 100 mg.kg -1 (22.5 ± 6 .0) and 200 mg.kg-1 (28.5 ±5.3) relative to the vehicle-treated group (41.6 ±1.1). In the hot plate model, at times of 30, 60 and 120 minutes, the animals treated with THL 50 mg.kg-1 (14.0 ± 0.6 s; 14.0 ± 0.1 s; 5.6 ± 1.4 s), 100 mg.kg-1 (10.8 ± 1.5 s; 8.6 ± 1.5 s; 6.6 ± 0.9 s) and 200 mg.kg-1 (10, 5 ± 1.1 s; 9.4 ± 1.4 s; 11.8 ± 1.0 s) showed a significant increase in latency for the nociceptive response, in a dose-dependent manner, when compared to the vehicle-treated group (4,333 ± 0.2108 s; 1.0 ± 0 s; 1.0 ±0.0 s, respectively). Finally, in the formalin model, the monoterpene significantly reduced paw licking time, in both phases, at doses of 50 mg.kg -1 (11.8 ± 2.9 s; 115.6 ± 18.0 s ), 100 mg.kg -1 (15.6 ± 1.5 s; 127.0 ± 34.1 s) and 200 mg.kg -1 (29.6 ± 2.4 s; 172.7 ± 13, 8 s) compared to the vehicle-treated group (51.6 ± 10.2 s; 281.5 ± 31.2 s). This latter effect was partially reversed by naloxone, a competitive opioid receptor antagonist. In view of the results obtained, THL proved to be a safe molecule, being devoid of effect on the motor coordination of the animals and showed antinociceptive activity at peripheral and central levels, the latter being dependent, at least in part, on opioid neurotransmission.